Eksistensi dan Perlindungan Hukum Jabatan Kepala Lingkungan di Kabupaten Buleleng - Remaja, I Nyoman Gede; Sandiasa, Gede; Ary Sri Tjahyanti, Luh Putu (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to analyze the existence and legal protection of the position of neighborhood head in the regional governance of Buleleng Regency. This study used a sociological juridical approach conducted in three areas: Buleleng District, Sukasada District, and Seririt District. Data collection techniques in this study include documentation, interviews, and questionnaires. Data analysis used qualitative and quantitative techniques. The results of the study indicate that the existence of neighborhood heads in Buleleng Regency plays a role in assisting village heads in services and decision-making at the village level, even though their employment status is only as contract workers. The role of neighborhood heads is not listed in the official village structure based on Government Regulation Number 17 of 2018, but remains a strategic partner in the implementation of government and public services. Legal protection for the position of neighborhood heads in Buleleng Regency lacks legal certainty, due to the lack of clear regulations. The position of neighborhood heads has the potential to cause legal problems in the future, so a legal basis is needed through regional regulations to ensure legal certainty, protect officials, and support the implementation of authority legally and effectively.